Brill's Companion to the Reception of Presocratic Natural Philosophy in Later Classical Thought - Harry, Chelsea C.; Habash, Justin (Brill's Companions to Philosophy, 2021)
"In Brill's Companion to the Reception of Presocratic Natural Philosophy in Later Classical Thought, contributions by Gottfried Heinemann, Andrew Gregory, Justin Habash, Daniel W. Graham, Oliver Primavesi, Owen Goldin, Omar D. Álvarez Salas, Christopher Kurfess, Dirk L. Couprie, Tiberiu Popa, Timothy J. Crowley, Liliana Carolina Sánchez Castro, Iakovos Vasiliou, Barbara Sattler, Rosemary Wright, and a foreword by Patricia Curd explore the influences of early Greek science (6-4th c. BCE) on the philosophical works of Plato, Aristotle, and the Hippocratics. Rather than presenting an unified narrative, the volume supports various ways to understand the development of the concept of nature, the emergence of science, and the historical context of topics such as elements, principles, soul, organization, causation, purpose, and cosmos in ancient Greek philosophy"--